Synergistic agronomic practices in redgram (Cajanus cajan) productivity and soil health enhancement under semi-arid tropics - P M SHANMUGAM (The Indian Journal of Agricultural Sciences)
An experiment was conducted during rainy (kharif) season of 2020 and 2021 at Tamil Nadu Agricultural University, Coimbatore, Tamil Nadu to study the impact of integrated phosphorus management in redgram (Cajanus cajan L.) intercropping systems under irrigated conditions. Redgram variety CO (Rg 7) was chosen as test crop. The experiment was laid out in a split-plot design (SPD) in three replications. The main plot comprised of intercropping systems, viz. sole redgram, redgram intercropped with soybean (Glycine max L.), greengram [Vigna radiata (L.) R. wilczek] and cowpea [Vigna unguiculata (L.) Walp.]. The sub plot consisted 3 forms of P, viz. Single super phosphate (SSP), enriched Mussoorie rock phosphate (MRP) + phosphobacteria and SSP (1/3rd) + enriched MRP (2/3rd) + phosphobacteria and 2 levels of P, viz. 50 and 62.5 kg P2O5/ha. The higher redgram grain equivalent yield (1207 kg/ha), net return (₹51,810/ha) and B: C ratio (2.74) were recorded under redgram intercropped with greengram followed by redgram intercropped with soybean, with corresponding values of 1,077 kg/ha, ₹48,141/ha and 2.29, respectively. With regards to various sources of P tried, integrated application of SSP (1/3rd) and enriched MRP (2/3rd) with phosphobacteria registered higher yield (957 kg/ha) of redgram, which was comparable with application of SSP. Regarding levels of P, application of 125% of recommended P (62.5 kg P2O5/ha) was recorded higher yield in redgram over 100% of recommended P (50 kg P2O5/ha) over the years. Considering the overall monetary returns of different redgram intercropping systems, application of 62.5 kg P2O5/ha in combination as SSP (1/3rd) + enriched MRP (2/3rd) along with phosphobacteria to redgram + greengram intercropping registered higher net return and B: C ratio.